Mesenchymal stem cell-based therapy for non-healing wounds due to chronic limb-threatening ischemia: A review of preclinical and clinical studies - Huerta, Carlos Theodore; Voza, Francesca A.; Ortiz, Yulexi Y.; Liu, Zhao-Jun; Velazquez, Omaida C. (Frontiers in Cardiovascular Medicine, 2023)
Progressive peripheral arterial disease (PAD) can result in chronic limb-threatening ischemia (CLTI) characterized by clinical complications including rest pain, gangrene and tissue loss. These complications can propagate even more precipitously in the setting of common concomitant diseases in patients with CLTI such as diabetes mellitus (DM). CLTI ulcers are cutaneous, non-healing wounds that persist due to the reduced perfusion and dysfunctional neovascularization associated with severe PAD. Existing therapies for CLTI are primarily limited to anatomic revascularization and medical management of contributing factors such as atherosclerosis and glycemic control. However, many patients fail these treatment strategies and are considered "no-option", thereby requiring extremity amputation, particularly if non-healing wounds become infected or fulminant gangrene develops. Given the high economic burden imposed on patients, decreased quality of life, and poor survival of no-option CLTI patients, regenerative therapies aimed at neovascularization to improve wound healing and limb salvage hold significant promise. Cell-based therapy, specifically utilizing mesenchymal stem/stromal cells (MSCs), is one such regenerative strategy to stimulate therapeutic angiogenesis and tissue regeneration. Although previous reviews have focused primarily on revascularization outcomes after MSC treatments of CLTI with less attention given to their effects on wound healing, here we review advances in pre-clinical and clinical studies related to specific effects of MSC-based therapeutics upon ischemic non-healing wounds associated with CLTI.